Collaborative learning across physical and virtual worlds: Factors supporting and constraining learners in a blended reality environment. (17th March 2016) - Bower, Matt; Lee, Mark J. W.; Dalgarno, Barney
Abstract: This article presents the outcomes of a pilot study investigating factors that supported and constrained collaborative learning in a blended reality environment. Pre‐service teachers at an Australian university took part in a hybrid tutorial lesson involving a mixture of students who were co‐located in the same face‐to‐face (F2F) classroom along with others who were participating remotely via their avatars in a three‐dimensional virtual world. Video and sound recording equipment captured activity in the classroom, which was streamed live into the virtual world so the remote participants could see and hear their instructor and F2F peers; the in‐world activity was also simultaneously displayed on a projector screen, with the audio broadcast via speakers, for the benefit of the F2F participants. While technical issues constrained communication and learning in some instances, the majority of remote and F2F participants felt the blended reality environment supported effective communication, collaboration and co‐presence. Qualitative analysis of participant evaluations revealed a number of pedagogical, technological and logistical factors that supported and constrained learning. The article concludes with a detailed discussion of present and future implications of blended reality collaborative environments for learning and teaching as well as recommendations for educators looking to design and deliver their own blended reality lessons.